Melanocortin Peptide Therapy for the Treatment of Arthritic Pathologies. (2009) - Getting, S. J.; Kaneva, M.; Bhadresa, Y.; Renshaw, D.; Leoni, Giovanna; Patel, H. B.; Kerrigan, M. J. P.; Locke, I. C.
Abstract : Arthritic pathologies are a major cause of morbidity within the western world, with rheumatoid arthritis affecting approximately 1% of adults. This review highlights the therapeutic potential of naturally occurring hormones and their peptides, in both arthritic models of disease and patients. The arthritides represent a group of closely related pathologies in which cytokines, joint destruction, and leukocytes play a causal role. Here we discuss the role of naturally occurring pro-opiomelanocortin (POMC)-derived melanocortin peptides (e.g., alpha melanocyte stimulating hormone [a-MSH]) and synthetic derivatives in these diseases. Melanocortins exhibit their biological efficacy by modulating proinflammatory cytokines and subsequent leukocyte extravasation. Their biological effects are mediated via seven transmembrane G-protein-coupled receptors, of which five have been cloned, identified, and termed MC1 to MC5 . Adrenocorticotrophic hormone represents the parent molecule of the melanocortins; the first 13 amino acids of which (termed a-MSH) have been shown to be the most pharmacologically active region of the parent hormone. The melanocortin peptides have been shown to display potent anti-inflammatory effects in both animal models of disease and patients. The potential anti-inflammatory role for endogenous peptides in arthritic pathologies is in its infancy. The ability to inhibit leukocyte migration, release of cytokines, and induction of anti-inflammatory proteins appears to play an important role in affording protection in arthritic injury, and thus may lead to potential therapeutic targets.